IMPROVING ARABIC SPEAKING SKILLS THROUGH LANGUAGE ART EXHIBITION - Yasin, Agus; Rochmat, Cecep Sobar; Syahida, Sofia Putri; Safira, Anastasya; Tazakka, Shabrina (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The purpose of this study was to determine the application of the Language Art Exhibition event at Modern Islamic Boarding School Darussalam Gontor for Girls First Campus and the effect of the Language Art Exhibition event on the speaking skills of grade 2. This type of research is quantitative research with a survey method at Modern Islamic Boarding School Darussalam Gontor for Girls First Campus. Researchers want to know the effect of Language Art Exhibition as variable X on Arabic speaking skills as variable Y. Based on the data generated, it can be concluded that this event has an effect on self-improvement and development as well as vocabulary development with its direct application and there is an influence on Language Art Exhibition (X) on Arabic speaking skills (Y) in grade 2 of Modern Islamic Boarding School Darussalam Gontor for Girls First Campus.